KONTRIBUSI WANITA TANI PENYADAP KARET TERHADAP PENINGKATAN PENDAPATAN KELUARGA DI DESA PASIR UTAMA KECAMATAN RAMBAH HILIR KABUPATEN ROKAN HULU - Kiagus Muhammad Basriwijaya (Universitas Mulawarman, 2019)
The role of women farmers in rural areas is very important, in addition to taking care of the household and the children of women farmers also work to earn additional income for their families, various types of work can be done by a woman both self-employed and farming. In this study jobs occupied by women farmers are tapping rubber (cut). Techniques of data collection using surveys and interviews. Data analysis technique used is quantitative analysis. Results of a study of the role of women farmers to the family income in the Pasir Utama Village In Sub District Rambah Rokan Hulu Regency contributed revenue of Rp. 10.977.559/ year and accounted for 31,98% of total revenues family. The revenue is no separation with her husband acceptance. In addition to acceptance of the peasant woman's husband's income is used to meet household needs. These needs include basic daily needs, the needs of school children and other social needs such as gathering and help people who have a celebration.